Analysis of Reinforced Concrete Pipe Strain Due to Jacking Force Case Study: Sudetan Ciliwung River Project to the East Flood Canal - Ayun, Zaimah Qurrata; Awaludin, Ali; Siswokarto, Suprapto; Ismanti, Sito (Universitas Negeri Padang, 2024)
Pipe Jacking is an innovation in trenchless technology that has been utilized in various sectors including municipal wastewater systems, oil and gas transportation, and hydraulic engineering. One of the critical aspects to ensure the success and safety of the pipe jacking process is strain monitoring. This study discussed the strain characteristics of reinforced concrete pipe structures during pipe jacking. The analysis was conducted using a numerical approach, which compared to field monitoring. Field strain monitoring was performed by strategically placing strain gauges along the pipe during the jacking operation, resulting in real-time data on deformation and pressure values. When the strain was monitored, the numerical test was conducted simultaneously using finite element analysis of Rocscience 3D. Those activities were done to consider the interaction between the reinforced concrete pipe and the surrounding soil. The strain analysis results indicated that the pipe responded during the pipe jacking process. The values of strain were various, depending on jacking force, condition of excavated soil layers, and distance between twin tunnels. The maximum stress occurred at the beginning of jacking process, when the pipe infiltrated into the soil with stress value of 512 kPa.